Uso de blogs na formação inicial de professores de química a distância : benefícios e barreiras - Barro, Mario Roberto (2015)
Investigations concerning pre-service teacher education in Chemistry have increasingly been made from the 1990s. Currently, studies that are based on reflective teaching are at the forefront. An alternative to creating a space for future teachers to reflect and discuss is setting up communities on the Internet using blogs. However, research aimed at using blogs in pre-service teacher education in chemistry in Brazil is scarce. In this work, we develop studies concerning the use of blogs in subjects related to the Curriculum stage and Teaching Practice in chemistry, taught on a long distance pre-service teacher education in chemistry. Therefore, we provide space on the blogs to publish and discuss activities carried out in lessons. Data was collected from publications on the blogs and by distributing questionnaires on the concept of teaching, as well as the use and acceptance of technology. We analysed the contributions of using blogs as a support tool for subjects, the evolution of the undergraduates’ teaching models and the perceptions of using blogs. We also detected and classified the levels of the undergraduates’ reflections concerning actions taken during the stages. Based on data analysis, changes from the future teachers’ previous conceptions could be observed regarding teaching and the acceptance of using blogs in education. Furthermore, using blogs helped the undergraduates to share, discuss and reflect on the activities of the subjects and actions taken in the curriculum stage. Finally, based on an extensive literature review carried out for this research and the results from it, we consider the benefits provided by the blogs in the context of pre-service teacher education, as well as the barriers that hinder its use.